Aldeamento de guerra no colonialismo português na Guiné-Bissau - Rui Aristides Lebre; Tiago Castela (e-cadernos ces)
This essay questions the villagization camp as a space of incarceration in late European colonialism, as well as its legacy for post-independence states. The research on which it is based focuses on the networks of rural camps created in occupied territories in Africa and Asia by several North Atlantic states for the forced resettlement of peasants, in order to try to avoid the progress of liberation movements. In particular, the essay explores the history of the network created by Portugal’s Army in the late 1960s and early 1970s in present-day Guinea-Bissau, taking into account that many camps became small towns after independence. It reflects on the military archive through a perspective informed by postcolonial theories, simultaneously proposing questions inspired by contemporary spatiality in Africa.